Penggunaan Metode Rolling Sphere untuk Pengamanan Jaringan 150 kV dari Sambaran Petir Langsung - Irrine Budi Sulistiawati; M Zaid Sahlan Shaufi; I Made Wartana (Universitas Darul Ulum, 2023)
Lightning strikes can cause protection failure at substations such as equipment damage at substations due to insulation failure or what is known as flashover. Because of that, a lightning strike protection system is needed to minimize the occurrence of direct lightning strikes to equipment and buses at the substation. This study discusses the modeling of the protection of the substation from direct lightning strikes using the rolling sphere method at the Wonosari-pedan 150 kV substation using lightning rod poles. The calculation results show that with the configuration of a lightning rod as high as 21 m and the use of a ground wire of 17.8 m it meets the safe criteria for the height of the protected area in the case study of this research.